Modeling a Virtual World for the Educational Game Calangos. (24th April 2014) - Loula, Angelo C.; de Castro, Leandro N.; Apolinário, Antônio L.; da Rocha, Pedro L. B.; Carneiro, Maria da Conceição L.; Reis, Vanessa Perpétua G. S.; Machado, Ricardo F.; Sepulveda, Claudia; El-Hani, Charbel N.
Abstract : Ecology plays a central role in biology and deserves special attention in scientific education. Nonetheless, the teaching and learning of ecology face a number of difficulties. In order to tackle these difficulties, electronic games have recently been used to mediate ecology learning. This paper presents an electronic game that fulfills these gaps in order to make the students' work with ecological concepts more concrete, active, and systematic. The paper presents the computational model of the ecological system included in the game, based on a real ecological case, a sand dune ecosystem located in the semiarid Caatinga biome, namely, the sand dunes of the middle São Francisco River, in the state of Bahia, Brazil. It includes various ecological relationships between endemic lizards and the physical environment, preys, predators, cospecifics, and plants. The engine of the game simulates the physical conditions of the ecosystem (dune topography and climate conditions with their circadian and circannual cycles), its biota (plant species and animal species), and ecological relationships (predator-prey encounters, cospecific relationships). We also present results from one classroom study of a teaching sequence structured around Calangos, which showed positive outcomes regarding high school students' understanding of thermal regulation in ectothermic animals.